EASL versus LI‐RADS: Intra‐individual comparison of MRI with extracellular contrast and gadoxetic acid for diagnosis of small HCC. (20th July 2021) - Min, Ji Hye; Kim, Jong Man; Kim, Young Kon; Kim, Honsoul; Cha, Dong Ik; Kang, Tae Wook; Choi, Gyu Seong; Choi, Seo‐Youn; Ahn, Soohyun
Abstract: Background & Aims: Liver Imaging Reporting and Data System (LI‐RADS) and European Association for the Study (EASL) criteria for hepatocellular carcinoma (HCC) diagnosis have been updated in 2018. We aimed to compare the HCC diagnostic performance of LI‐RADS and EASL criteria with extracellular contrast agents‐MRI (ECA‐MRI) and hepatobiliary agents‐MRI (HBA‐MRI). Methods: We prospectively evaluated 179 participants with cirrhosis (n = 105) or non‐cirrhotic chronic hepatitis B (CHB) (n = 74) who underwent both ECA‐MRI and HBA‐MRI before surgery for de novo nodule(s) measuring 10‐30 mm. We compared the HCC diagnostic performance of EASL and LR‐5 in both MRIs. Results: In an analysis of 215 observations (175 HCCs, 17 non‐HCC malignancies and 23 benign lesions) identified from cirrhotic or non‐cirrhotic CHB participants, LR‐5 with ECA‐MRI provided the highest sensitivity (80.7%), followed by EASL with ECA‐MRI (76.2%), LR‐5 with HBA‐MRI (67.3%) and EASL with HBA‐MRI (63.0%, all P  < .05). The specificities were comparable (89.4%‐91.5%). When the analysis is limited to participants with pathological cirrhosis (123 observations), the sensitivity of LR‐5 with ECA‐MRI was similar to that of EASL with ECA‐MRI (82.7% vs 80.2%, P  = .156), but higher than LR‐5 with HBA‐MRI (65.1%) or EASL with HBA‐MRI (62.8%, both P  < .001), with comparable specificities (87.5%‐91.7%). Conclusions: The LR‐5 with ECA‐MRI yielded the highest sensitivity with a similar specificity for HCC diagnosis in cirrhosis and non‐cirrhotic CHB participants, while the sensitivities of LR‐5 and EASL with ECA‐MRI are similar for cirrhosis participants. This indicates non‐invasive diagnosis criteria can differ by contrast agents and presence of cirrhosis.